Perbedaan Kualitas Kompos Berbahan Dasar Limbah Baglog Jamur Tiram dan Kotoran Ayam - Untung Santoso; Zulaikha Zulaikha; Rabiatul Wahdah (Universitas Lambung Mangkurat, 2021)
Oyster mushroom is a common edible mushroom and grown commercially around the world for food. As the increasing of the cultivation go hand in hand with the increasing production of the mushroom, however, it also means an increase of waste of media growing mushrooms were produced. Oyster mushroom baglog waste is merely discarded and unutilized, so it will become a pile of garbage and pollute the environment. In reducing the amount of waste of it is to make it compost. The purpose of this study was to determine differences in the quality of compost made from baglog oyster mushroom waste and chicken manure with several SNI parameters. This research is a descriptive method by looking at differences in the quality of compost made from baglog waste and chicken manure, specifically : k1 = 4 kg baglog waste + 3 kg chicken’s manure, k2 = 5 kg baglog waste + 2 kg chicken’s manure, k3 = 6 kg baglog waste + 1 kg of chicken’s manure. This research was conducted in 3 stages, in specific: (i) Preparation, (ii) Implementation of composting, (iii) Observation and data processing. The results of this study there are differences in the quality of compost made from 5 kg baglog oyster mushroom waste + 2 kg chicken manure gives the best results for C-Organic, N-Total, P-Total, K-Total, C / N Ratios and pH that meets SNI.